Building Containerized Workflows Using the BioDepot-Workflow-Builder - Hung, Ling-Hong; Hu, Jiaming; Meiss, Trevor; Ingersoll, Alyssa; Lloyd, Wes; Kristiyanto, Daniel; Xiong, Yuguang; Sobie, Eric; Yeung, Ka Yee (Cell systems, 2019)
We present the BioDepot-workflow-builder (Bwb), a software tool that allows users to create and execute reproducible bioinformatics workflows using a drag-and-drop interface. Graphical widgets represent Docker containers executing a modular task. Widgets are linked graphically to build bioinformatics workflows that can be reproducibly deployed across different local and cloud platforms. Each widget contains a form-based user interface to facilitate parameter entry and a console to display intermediate results. Bwb provides tools for rapid customization of widgets, containers, and workflows. Saved workflows can be shared using Bwb's native format or exported as shell scripts.